PEMBINAAN IBU RUMAH TANGGA UNTUK MENDUKUNG PEREKONOMIAN KELUARGA MELALUI USAHA PEMBUATAN BROS - hikmah hikmah; Ade Wilda Damanik (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2019)
Some housewives in Batam City do not work, relying solely on income from their husbands. During this time, housewives use their free time to socialize and have a good time with their neighbors without producing anything useful, so it's time to take advantage of these habits in order to produce something to support their family's economy. In order for income housewives to have new knowledge and abilities, crafting activities are carried out by using patchwork. This training is carried out to use patchwork to have more selling value such as hijab accessories. This training was carried out twice, which was given the understanding of housewives about the use of patchwork and then given the practice of learning by doing. In the implementation of the service carried out by practicing directly how to make a brooch with several models of patchwork. Aside from the guidance of making brooches from patchwork, researchers also provide assistance in managing financial management, so that in the future it can be used as a home business that can help support the family's economy. From the results of the evaluation at the service of the mothers, thousands of households have been able to make patchwork brooches with several variations and models